PENERAPAN METODE TILAWATI DALAM MENINGKATKAN KEMAMPUAN MEMBACA Al-QUR’AN TAMAN PENDIDIKAN AL-QUR’AN DI DESA JERUK SOK-SOK KECAMATAN BINAKAL KABUPATEN BONDOWOSO - Novidatur Rizkiyah; Chalimatus Sa’diyah; Adi Sudrajat (VICRATINA, 2020)
The background of establishment Al-Qur’an Education Park (TPQ) is generally caused by varios factors, including the limited hours of education in schools and the lack attention of parents in educating their children, especially in the field of religion. The study aims to determine how thestategy applying method of tilawati  learning process of reading Qur’an at the TPQ Darus Sholah Binakal Bondowoso. To simplify this research the researchers used a qualitative approach using three data collection techniques namely, observation, interviews and documentation. From result of this study the researchers found that: first, in TPQ Darus Sholah  the learning process using tilawati method, mastering tilawati method, mastering learning theories, second, the learning process tilawati using classical and individual techniques, the application seating positions in the form circle to make it easier for teachers control state of students during the learning process, third, the problems faced by  teacher are the attitude students who are note polite and lack of concentration during the learning process, the teacher plays and important role, learing will run smoothly if the learing program is well structured, as for the inhibiting and supporting factors of the process of applying this tilawati method come from teachers, students, and the environment.